The Captain's guide to : alternative energy afloat - The Captain's guide to ([Place of publication not identifed] : Seaworthy Publications, 2019)
A successful ocean passage on a small to midsize sailing vessel means keeping things as simple as possible. Sun, Wind, and Water : The Essential Guide to the Energy-Efficient Cruising Boat gives you the most detailed, up-to-date advice on how to prepare your boat for an ocean crossing while at the same time saving money and ensuring a smaller footprint on Mother Nature.
Main power plant -- Engine alternators -- Gas and diesel generator sets -- Alternative fuels -- Cranking and house batteries -- Solar panels -- Wind generators -- Hydro generators -- Voltage regulators and controllers -- Monitoring systems -- Lighting, navigation, and communication -- Refrigeration -- Windvane self-steering -- Autopilots -- Manual windlasses -- Electric windlasses -- Tools, spare parts, and maintenance supplies -- The essence of green voyaging -- Energy efficiency : three cruising yachts -- References -- Appendix 1: AWG battery cable sizes -- Appendix 2: AWG wire gauge sizes -- Appendix 3: Beaufort scale -- Appendix 4: Cruiser's Ham bands -- Appendix 5: Marine fire extinguishers -- Appendix 6: Sailboat specifications decoded.
Includes bibliographical references and index.
Keywords: YACHTING